2018
DOI: 10.4103/ijph.ijph_258_18
|View full text |Cite
|
Sign up to set email alerts
|

Sun exposure and Vitamin D in rural India: A cross-sectional study

Abstract: Proper information, education, and communication material regarding various aspects of sun exposure and Vitamin D should be prepared with due consultation of field experts and disseminated to increase awareness among the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…A huge number of safe cryogenic transportation containers and networks, Oxygen concentrators, and PSA (Pressure swing adsorption) in oxygenproducing plants are required. Also, nobody can give a guarantee of no other waves in the future, https://pib.gov.in/PressReleseDetailm.aspx?PRI D=1717459, Mohammad A, [31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…A huge number of safe cryogenic transportation containers and networks, Oxygen concentrators, and PSA (Pressure swing adsorption) in oxygenproducing plants are required. Also, nobody can give a guarantee of no other waves in the future, https://pib.gov.in/PressReleseDetailm.aspx?PRI D=1717459, Mohammad A, [31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…In rural and remote hospitals and healthcare institutions, solar-powered oxygen systems can be installed on a broad scale and have been linked to a decrease in child fatalities and a reduction in referrals ( 88 ). According to Madaan et al ( 89 ), rural India’s oxygen needs should focus on employing a supply of substantially pure oxygen that is secure, affordable, simple to access, and mass-producible. The arrangement of a self-sustaining oxygen concentrator (pressure swing adsorption with multiple molecular sieve technology) that provide oxygen at high flow rates through a centrally controlled distribution network to 100 or even more bedded community hospitals, with backup from an oxygen bank of 10 × 10 cylinders, may be able to achieve this.…”
Section: Supportive Data Regarding Utilization Of Oxygen Concentratorsmentioning
confidence: 99%
“…The arrangement of a self-sustaining oxygen concentrator (pressure swing adsorption with multiple molecular sieve technology) that provide oxygen at high flow rates through a centrally controlled distribution network to 100 or even more bedded community hospitals, with backup from an oxygen bank of 10 × 10 cylinders, may be able to achieve this. It could also act as a facility for replenishing local oxygen cylinders for medical emergencies inside the hospital premises and for delivery to ambulances, primary health centers, and other remote locations ( 89 ).…”
Section: Supportive Data Regarding Utilization Of Oxygen Concentratorsmentioning
confidence: 99%
“…A central bank of oxygen cylinders should be created in communities with a high number of cases in order to ensure adequate delivery for patients undergoing home and community isolation. 9 However, any community oxygen bank must be implemented in parallel with strong safety measures of setting up the system. Table 2 summaries the advantages and limitations of each oxygen modality based on the capacity of oxygen equipment and its use in diverse health care settings.…”
Section: Oxygen Generator and Oxygen Concentratormentioning
confidence: 99%
“…In addition, experiences from other regions such as India and sub-Saharan Africa showed that during the peak of the pandemic, it is critical to have a clear plan on oxygen supply in response to COVID-19. [9][10][11] This article thus investigated the situation of medical oxygen supply for COVID-19 patients in Thailand based on both supply and demand perspectives, and aimed to provide optimal recommendations for a better management of oxygen supply in Thailand in response to the COVID-19 pandemic. The model also relied on the following assumptions.…”
Section: Introductionmentioning
confidence: 99%